2008
DOI: 10.1093/ee/37.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Associations of Ant Species (Hymenoptera: Formicidae) in a Heterogeneous Mississippi Landscape

Abstract: Community assembly and the factors that influence it have long been a topic of interest to ecologists, but theory has yet to produce unequivocal evidence that communities assemble in predictable ways. The goal of this study was to document the relationship between ant communities and environmental variation between four habitat types. To accomplish this, ant communities and 16 environmental variables were sampled across four different habitat types in the Black Belt Prairie and Flatwoods regions in Mississippi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…Other studies also show changes in ant species composition among different habitat types (Lassau and Hochuli, 2004;Lassau et al, 2005;Hill et al, 2008;Barrow and Parr, 2008). Although these authors reported that the differences may be an outcome of interactions, mainly resource competition, we think that competition may not be the only factor to explain our results.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Other studies also show changes in ant species composition among different habitat types (Lassau and Hochuli, 2004;Lassau et al, 2005;Hill et al, 2008;Barrow and Parr, 2008). Although these authors reported that the differences may be an outcome of interactions, mainly resource competition, we think that competition may not be the only factor to explain our results.…”
Section: Discussionmentioning
confidence: 48%
“…The response of the ant species to particular habitat types has been demonstrated to be related to vegetation complexity, both negatively (Lassau and Hochuli, 2004) and positively (Lassau et al, 2005;Hill et al, 2008). However, the relationship between local-community diversity and assemblage composition may be influenced by factors acting at other scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also investigated the response of the invasive S. invicta to grazing to conÞrm whether or not this Þre ant is more abundant in disturbed (grazed) habitats in its native range, as has been reported for its introduced range, mainly in North America Tschinkel 2006, 2008;Hill et al 2008). …”
mentioning
confidence: 99%
“…The orchard label is composed of letters indicating the localities in which the orchard is located (T = Thiès, P = Pout, N = Notto, Nd = Ndoyenne), followed by a number standing for the orchard type according to the typology based on orchard design and management practices: (1) 'no-input mango diversified orchards', (2) 'low-input mango orchards, (3) 'medium-input citrus-predominant orchards' and (4) 'medium-input large mango-or citrus-predominant orchards'. (Ribas et al, 2003;Hill et al, 2008;Pacheco and Vasconcelos, 2012;De la Mora et al, 2013) and their decline in landscapes subject to high management intensity (Ribas and Schoereder, 2007;House et al, 2012). The greatest tree richness and coefficient of variation for the local planting density observed in the type (3) orchards created microenvironmental diversity generated by the existence of empty spaces and plant-mosaic portions in those orchards.…”
Section: Ant Diversity Ant Richness and Relations With Orchard Typementioning
confidence: 99%